Nietzsche's posthumanism - Landgraf, Edgar, 1967- (Posthumanities ;, 2023)
"Nietzsche's Posthumanism explores the continuities and disagreements between Nietzsche's philosophy and contemporary posthumanism. Focusing specifically on Nietzsche's reception of the life sciences of his day and his reflections on technology, Edgar Landgraf provides both fresh readings of Nietzsche and a critique of post- and transhumanist philosophies"--